Young Music Makers - The Star, Yam Phui Yee (2008)
Tham Hong Kent used to wait for everyone to leave the church after Sunday service so be could tinker on the ivory keys of the piano. The music he played would lift him into hid own world, until hr was brought back to reality by the church caretaker asking him to leave.